Covid-19 infection reduction measures as a safety certification in the Spanish tourism sector - Sánchez-Arcediano, Sandra; Babinger, Frank (Revista de Estudios Andaluces, 2022)
The Covid-19 pandemic has transformed the world in general, and tourism in particular, and tourism destinations have made great efforts to integrate risk management. In this new framework, cooperation has proved essential to tackle the virus. Therefore, the main objective of the research is to identify the main measures carried out by and for the tourism sector to address Covid-19 and to check whether they have been elaborated as a possible certification. The research methodology was based, firstly, on a review of the existing literature on the concepts of tourism governance, cooperation and collaboration, tourism policy and standardization. Moreover, the measures carried out at national level for the tourism sector have been selected and analyzed, and the bodies involved in the development of these measures have been analyzed. The result achieved is that the measures carried out at national level for the tourism sector have proven to be effective, as they have resulted in a standard for Spanish tourist destinations, and their implementation is being promoted at international level.